Black Phosphorus/Hollow Porous Carbon for High Rate Performance Lithium‐Ion Battery. Issue 9 (11th May 2020) - Zhou, Shijie; Li, Jia; Fu, Licai; Zhu, Jiajun; Yang, Wulin; Li, Deyi; Zhou, Lingping
Abstract: Black phosphorus (BP) has received wide attention due to its high theoretical capacity (2596 mAh g −1 ) and good electron mobility, but its cyclic stability is poor. Meanwhile, it can be complementary to carbon material, which has low theoretical capacity but good cycle stability. In this work, we use solvothermal reaction to modify hard carbon materials with black phosphorous (BP). When used as anode material for lithium‐ion batteries, the composite will show a higher specific capacity, cyclic stability and rate performance. It shows a high reversible capacity of 350 mAh g −1 after 1000 cycles at 1000 mA g −1 current density. But for pure carbon, it only shows a general reversible capacity of 180 mAh g −1 . Here, the lower content of black phosphorous and the use of hard carbon materials make the material more economically advantageous. And it can be used as an ideal material for cycling at high currents in the future. Abstract : A joint effort : Black phosphorus is supported on porous carbon in a bonded form through a simple solvothermal reactions. The resulting composites are far superior to pure carbon in terms of rate and cycle performance in Li‐ion batteries. Its economic applicability is also higher than that of phosphorus‐based materials.